Effect of ticagrelor on endothelial calcium signalling and barrier function - Gündüz, Dursun; Tanislav, Christian; Schluter, Klaus-Dieter; Schulz, Rainer; Hamm, Christian; Aslam, Muhammad (Thrombosis and Haemostasis, 2017)
The P2Y12 receptor is a Gi-coupled receptor whose activation inhibits adenylyl cyclase and thereby reduces the concentration of intracellular cAMP. Here the hypothesis was tested whether AR-C 66096 or ticagrelor, two direct-acting and reversibly binding P2Y12 receptor antagonists, protect endothelial cell (EC) barrier function by raising intracellular cAMP in ECs. The study was carried out on primary human umbilical vein ECs (HUVECs) and human pulmonary microvascular ECs (hPMECs). AR-C66096 (10 µM) induced a 50 % increase in cAMP in ECs whereas ticagrelor (2–10 µM) had no effect. Likewise, AR-C666096 antagonised thrombin-induced hyperpermeability in both HUVECs and hPMECs, but ticagrelor had no effect on basal EC monolayer permeability. Ticagrelor, however, sensitised ECs for thrombin-induced hyperpermeability and potentiated the thrombin effect. Ticagrelor but not AR-C66096 caused an increase in cytosolic calcium ([Ca2+]i). This increase in [Ca2+]i was abrogated by LaCl3 (Ca2+ influx inhibitor) but not by xestospongin C (IP3 receptor antagonist) or by depletion of intracellular stores with thapsigargin, suggesting a Ca2+ influx from the extracellular space. Accordingly, ticagrelor caused an increase in myosin light chain (MLC) phosphorylation, an important regulator of EC contractile machinery and thus permeability, which was abrogated by LaCl3. The ability of ticagrelor to potentiate EC permeability was abrogated by a MLC kinase inhibitor (ML-7; 10 µM). Our data demonstrate that the P2Y12 receptor antagonist AR-C66096 exerts a protective effect on ECs in vitro, possibly by raising intracellular cAMP, whereas ticagrelor sensitises EC barrier function by inducing Ca2+ influx and activating downstream EC contractile machinery.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: P2Y12 receptors; contractile machinery; AR-C66096; permeability; dipyridamole